Pharmacogenomics and its Role in Cardiovascular Diseases: A Narrative Literature Review - Kayani, Maryam; Sangeetha, Gadde Krishna; Sarangi, Swapna; Gaddamanugu, Leela Sarmada; Sharma, Shelja; Adedara, Victor O.; Abdallah, Saria; Katz, Kristina; Mora, Glendalys Rodríguez; Kommuru, Sravani; Nazir, Zahra (Current Cardiology Reviews, 2025)
Pharmacogenomics has transformed the way we approach the treatment of the most common diseases worldwide, especially cardiovascular. In this article, we highlight the main categories of drugs involved in major cardiovascular diseases (CVD), related genetic variability and their effects on metabolism in each case of contrastive operability. This not only explains disparities in treatment outcomes but also unfolds customised management based on genomic studies to improve efficiency and limit side effects. Genetic variations have been identified that impact the efficacy, safety, and adverse effects of drugs commonly used in the treatment of CVD, such as Angiotensin converting Enzyme Inhibitor (ACEI), Angiotensin Receptor Blocker (ARBs), calcium channel blockers, antiplatelet agents, diuretics, statins, beta-blockers, and anticoagulants. It discusses the impact of genetic polymorphisms on drug metabolism, efficacy, and adverse reactions, highlighting the importance of genetic testing in optimizing treatment outcomes. Pharmacogenomics holds immense potential for revolutionizing the management of CVD by enabling personalized medicine approaches tailored to individual genetic profiles. However, challenges such as clinical implementation, cost-effectiveness, and ethical considerations need to be addressed to completely incorporate pharmacogenomic testing into standard clinical practice. Continued research and clinical diligence are required for the utilization of pharmacogenomics to improve therapeutic outcomes and reduce the burden of CVD globally.
Keywords: calcium channel blockers